Les aménagements portuaires antiques de Pont-Sainte-Maxence (Oise) : premier bilan - Denis Maréchal (Gallia)
Pont-Sainte-Maxence (Oise) is located 52 km north-east of Paris on the course of the Oise river. As is the case today, the ancient city was located at the junction of the alluvial plain and a cut at the edge of the chalky plateau. Until 2014, there was no archaeological evidence of the existence of this city, which is located at the crossroads of a waterway and a major road (Lyon-Boulogne). The surveys carried out in 2014 and 2020 in an area encompassing 1.36 ha discovered a port development dated to the second half of the 1st c. AD. The quay was at least 70 m long and 7.50 m wide. Excavated up to a depth of 1.20 m, it consisted of two parallel walls (sometimes recovered) made up of large limestone blocks and perhaps of internal 4.40-meters-wide caissons. On the river side 0.05 to 0.10 m thick levels of tamped chalk were noted, with slopes estimated between 20 and 25°. These may be interpreted as being landing stages. Behind the quay there were several wall foundations, floor levels (without furniture) and rare structures, which could possibly be related to warehouses. The quay was abandoned prior to the mid-2nd c. AD. The ancient city was probably located about fifty metres away, five metres higher, on the first terrace of the river. This survey logically raises questions: were there platforms for other periods? Were these displaced? What was the scope of this development?